A prospective study in esophageal atresia with tracheoesophageal fistula: Oblique versus circular anastomosis - Mujalde, Vikram Singh; Barolia, Dinesh kumar; Gupta, Pradeep; Mehra, Sunil; Gupta, Arun (International Surgery Journal, 2018)
Background: Congenital esophageal atresia with tracheo-esophageal fistula is a common congenital anomaly facing at our centre. There is various proposed anastomotic technique to avoid post-op stricture. In this study we compare outcome of oblique and circular anastomosis technique at our centre. Methods: This study conducted in 60 cases of congenital esophageal atresia with tracheo-esophageal fistula, designed randomly in two groups. Oblique anastomosis in group A and Circular anastomosis in group B. The complications of anastomotic leaks, anastomotic narrowing with strictures and recurrent fistula were studied. Results: Anastomotic leak rate in case oblique anastomosis was 6.7% as compared to circular anastomosis was 16.7%. Stricture formation in oblique anastomosis was 13.3% in comparison to circular anastomosis there was 43.3% stricture formation. None of the cases required re-exploration in Oblique anastomosis, whereas two (6.7%) cases required re-exploration in circular anastomosis. Conclusions: Present study showed that oblique anastomotic technique is superior to circular anastomotic technique, in term of less stricture and leak rate.